The effects of hyperbaric oxygen exposure on recovery after high-intensity exercise - Horie, M.; Shimoda, M.; Imai, T.; Watanabe, K.; Enomoto, M.; Miyakawa, S.; Yagishita, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Hyperbaric oxygen therapy (HBO), which can dissolve oxygen in serum in population to atomic pressure and transport oxygen to ischemic tissue, is an established therapy for treatment of several conditions, including decompression illness, carbon monoxide poisoning, and acute artery occlusion. Recently, it has become an increasingly popular treatment for athletes suffering from muscle or ligament injury. However, the effect of HBO is not clear on recovery from sports activities. The purpose of this study is to determine how HBO exposure effects on physiological responses and recovery after high-intensity exercise in athletes. Methods: Healthy male volunteer subjects (age: 21.0 ± 1.2 years) were randomly divided into the two groups of the HBO group (n=11) and the non-HBO treatment (control; CT) group (n=11). All subjects underwent the highintensity cycle exercise of 75% heart rate max for 60 minutes. After the exercise, the subjects of HBO group were placed in hyperbaric chamber with inhalation of 100% oxygen at 2.5 atmospheres absolute (ATA) for 60 min. The total duration of the procedure was 120 min (including compression and decompression). The subjects of CT group seated rest for 120 min. Subjective evaluation of fatigue after exercise was assessed using a visual analogue scale (VAS). In addition, blood counts, blood lactate, serum IL-6 concentration, natural killer cell (NK) activity, and oxidative stress markers (d-ROM, BAP) were measured at pre-, post-exercise and after HBO or non-treatment. Results: VAS value was significantly increased after exercise, and decreased after HBO or non-treatment. VAS values in HBO group were lower than that in CT group after the treatment. In the blood test, serum IL-6 concentration was significantly increased after exercise in both groups and then significantly decreased after HBO treatment compared with that before HBO treatment. Lymphocyte was significantly increased after HBO treatment in HBO groups, but not changed in CT group. There were no differences between HBO and CT groups in terms of NK cell activity value, d-ROM, BAP and lactate. Discussion: The HBO treatment did not only reduce high-intensity exercise- induced fatigue, but also showed anti-inflammation response and high level of lymphocytes in the blood. These findings indicate that HBO treatment was effective for recovery from High-intensity exercise. As a next step, we need to clarify the physiological mechanisms of these effects by HBO treatment.